Prescriptive stretching - Berg, Kristian, 1964- (Human Kinetics, 2020)
"Prescriptive Stretching, 2E, includes instructions and illustrations for features full-color illustrations and instructions for 69 stretches to improve flexibility and reduce pain. Partner stretches and ball self-massage exercises have been added to this edition. It also includes 10 programs to address different body areas"